Implementasi Metode Simple Additive Weighting (SAW) Dalam Sistem Pendukung Keputusan Karyawan Teladan - Sofin Rendian Novianto; Imam Husni al Amin (STEKOM PRESS, 2023)
Employees are Human Resources who are very important to achieve the company's vision and mission. Employees have a significant impact on the company's growth and ability to compete in the market. One way to create quality human resources, we need a system to determine exemplary employees. One way to determine employees by using a decision support system. Decision support systems are made to determine exemplary employees in a company based on predetermined weights. The method used in this system is Simple Additive Weighting because it has the advantage of being able to determine the weight value of each attribute. The results obtained from calculations using this system are the names of exemplary employees who have been sorted according to their ranking from the top to the bottom and this system can be used by companies to make it easier to give rewards or appreciation in determining exemplary employees.